Tracing the Web:: House of Anansi’s Spiderline Editions - Cain, Stephen (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2000)
Established in 1969, the House of Anansi Press's Spiderline series represents a unique moment in Canadian publishing history. At no time previously had a Canadian publisher attempted to release the work of so many unknown and untried novelists simultaneously and also emphasize the fact that these were first, and perhaps not perfect, novels. Anansi's goals for the Spiderline series were to let new voices be heard, to give first-time novelists a chance at publication, and to get it done quickly by producing each of the Spiderlines with the same Spartan cover and identical typeface. All of the first five writers published — Peter Such, Russell Marois, Matt Cohen, John Sandman, and Pierre Gravel — were white, male, and no older than thirty. With its diverse collection of authors, experimental styles, and youthful enthusiasm for the new, the local, and the bilingual the original Spiderline books were the vision of Dennis Lee and David Godfrey at a time of great patriotism and literary expansion. The decision to reintroduce the Spiderline series in the late 1990s can be viewed as an attempt to regain Anansi's earlier status as a "progressive" and unique publishing enterprise.